Plant growth-promoting bacterium Pseudomonas fluorescens FR1 secrets a novel type of extracellular polyhydroxybutyrate polymerase involved in abiotic stress response in plants - Stritzler, Margarita; Diez Tissera, Ana; Soto, Gabriela; Ayub, Nicolás Daniel (Springer, 2018)
Objectives Identification of novel microbial factors contributing to plant protection against abiotic stress. Results The genome of plant growth-promoting bacterium Pseudomonas fluorescens FR1 contains a short mobile element encoding a novel type of extracellular polyhydroxybutyrate (PHB) polymerase (PhbC) associated with a type I secretion system. Genetic analysis using a phbC mutant strain and plants showed that this novel extracellular enzyme is related to the PHB production in planta and suggests that PHB could be a beneficial microbial compound synthesized during plant adaptation to cold stress. Conclusion Extracellular PhbC can be used as a new tool for improve crop production under abiotic stress.